2006
DOI: 10.1007/s11109-006-9005-6
|View full text |Cite
|
Sign up to set email alerts
|

“Racial Threat”, Partisan Climate, and Direct Democracy: Contextual Effects in Three California Initiatives

Abstract: Does context-racial, economic, fiscal, and political-affect whites' votes on racially-related ballot propositions? We examine non-Hispanic whites' voting behavior on three California ballot initiatives: Propositions 187, 209, and 227. Unlike previous analyses that lacked individual-level data and were therefore limited to ecological inference, we combine individual-level data from exit polls with county-level contextual variables in a hierarchical linear model. Racial/ethnic context affected whites' votes only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(103 citation statements)
references
References 40 publications
1
102
0
Order By: Relevance
“…Since the work of Allport and Key, numerous studies (many summarized in Table 1) have been undertaken at various geographic scales, examining a series of dependent variables including attitudes to racial minorities, Kitschelt, 1996;Mayer, 1995;Robinson, 1980;Sigelman & Welch, 1993;Surace & Seeman, 1967;Yancey, 1999 Biggs & Knauss, 2012;Bowyer, 2008;Ford & Goodwin, 2010;Harris, 2012 + French departements Kitschelt, 1995; Mayer, 1995 + U.S. counties Blalock, 1957;Branton & Jones, 2005;Eitle et al, 2002;Giles & Evans, 1986;Glaser, 1994;Hopkins, 2011;Key, 1949;Reed, 1972;Rocha et al, 2011;Stein, Post, & Rinden, 2000;Wright, 1976+ Hood & Morris, 1997, 2000Morris, 2000− Corzine et al, 1983Dixon, 2006;Newman & Johnson, 2012 +/− Campbell, Wong, & Citrin, 2006= Louisiana Parishes Giles & Buckner, 1993Giles & Hertz, 1994;Voss, 1996 + Metropolitan areas Arp et al, 1999;Dixon, 2006;Fossett & Kiecolt, 1989;Jacobs & Carmichael, 2001, 2002Rocha & Espino, 2009;Taylor, 1998+ Ha, 2010+...…”
Section: Variation By Geographic Levelmentioning
confidence: 99%
“…Since the work of Allport and Key, numerous studies (many summarized in Table 1) have been undertaken at various geographic scales, examining a series of dependent variables including attitudes to racial minorities, Kitschelt, 1996;Mayer, 1995;Robinson, 1980;Sigelman & Welch, 1993;Surace & Seeman, 1967;Yancey, 1999 Biggs & Knauss, 2012;Bowyer, 2008;Ford & Goodwin, 2010;Harris, 2012 + French departements Kitschelt, 1995; Mayer, 1995 + U.S. counties Blalock, 1957;Branton & Jones, 2005;Eitle et al, 2002;Giles & Evans, 1986;Glaser, 1994;Hopkins, 2011;Key, 1949;Reed, 1972;Rocha et al, 2011;Stein, Post, & Rinden, 2000;Wright, 1976+ Hood & Morris, 1997, 2000Morris, 2000− Corzine et al, 1983Dixon, 2006;Newman & Johnson, 2012 +/− Campbell, Wong, & Citrin, 2006= Louisiana Parishes Giles & Buckner, 1993Giles & Hertz, 1994;Voss, 1996 + Metropolitan areas Arp et al, 1999;Dixon, 2006;Fossett & Kiecolt, 1989;Jacobs & Carmichael, 2001, 2002Rocha & Espino, 2009;Taylor, 1998+ Ha, 2010+...…”
Section: Variation By Geographic Levelmentioning
confidence: 99%
“…Even during times of economic growth, individuals may believe that undocumented immigrants are taking jobs away from native-born citizens (Neal and Bohon 2003), but this may be particularly heightened during economic stagnation or recession. There are conflicting findings on the effect of economic threat, with some research finding no evidence for the impact of local unemployment rates, personal income, and employment status on immigration policy preferences (Campbell et al 2006). Others have concluded that attitudes are in fact influenced by a sense of competition within the labor market with findings showing income (Palmer and Davidson 2011;Pérez 2010) and contextual economic factors (Berg 2009;Scheve and Slaughter 2001) as significant predictors of immigration attitudes.…”
Section: Prior Literaturementioning
confidence: 99%
“…From this item, we created a dichotomous variable, labeled Delay Welfare Benefits, and coded 1 for respondent's preferring the more restrictive position of making immigrants wait one year for benefits and 0 for those preferring to make immigrants immediately eligible for services. This item has been used in prior opinion research on immigration 32 and provides 28 Brader, Valentino and Suhay 2008;Campbell, Wong, and Citrin 2006;Hood and Morris 1997;Rocha and Espino 2009;Stein, Post, and Rinden 2000;Tolbert and Grummel 2003. 29 In addition to being consistent with prior research, extant research suggests that theoretical models other than those developed to explain national majority group reactions to immigrant minorities may be appropriate for explaining the dynamics of opinion on immigration among immigrants and other minority groups (e.g., Hainmueller and Hopkins 2014;Dancygier and Saunders 2006;Nteta 2013).…”
mentioning
confidence: 99%